Quantification of deformation trends in a sublevel caving mine using mobile 3D laser scanning - Gökdemir, Tamer (2021)
The Malmberget mine shows, in its great geological variety some weak rock zones consisting mainly of granites with biotite schist inclusions in the footwall as well as in the crosscuts, which forced the mine to stop mining in some drifts and invest in supplementary support and blasting of the floor to keep the tunnels open. Therefore, the mine is seeking to better understand the linkage between underground production, mining-induced stresses and deformation in different geologic structures encountered. The conducted research assesses trends in deformation based on geotechnical parameters in three orebodies with a mobile LiDAR system, namely the uGPS Rapid Mapper™, to gain a higher understanding of current deformations. By doing that also the real-life capabilities of the scanning system were observed. The study started with a comprehensive literature review about rock mass classification systems, deformation in underground excavations and mobile laser scanning in an underground environment to be at the current state of research. The further scope includes several hundred scans in areas that are prone to deformation for testing the repeatability and accuracy of the mobile scanner as well as detecting trends in deformation. Additionally, field observations regarding deformation changes, damages, water inflows and occurrence of additional reinforcement measures were collected. The designed tests and conducted scans showed that the uGPS Rapid Mapper™ works within the known parameters. The intention to detect and track deformation on a regular basis with little work power is given. Also, the immediate 3D visualization proved to be valuable for interpreting data. Deformation commonly occurs in grey leptite with an elevated content of biotite schist intrusions when the GSI is 10-35 and especially when adjacent a competent rock mass is present. This condition is often present at the ore contact zone. The research was able to further support suspected deformations and provide more accurate numbers of deformation. The ...